Extreme heat and acute air pollution episodes: A need for joint public health warnings?. (15th March 2021) - Pascal, Mathilde; Wagner, Vérène; Alari, Anna; Corso, Magali; Le Tertre, Alain
Abstract: Recent evidence suggests a synergistic acute effect between temperature, ozone and particulate matter (PM) on premature mortality. Several studies reported higher air pollution-related mortality risks during warm days, and higher heat-related mortality risk during polluted days. We investigated if interactions between temperature and air pollution modified the mortality response to an extent that would support the need for joint heat and air pollution warning systems. We developed a multicentre time-series design for 17 French cities for the period 2000–2015, investigating the influence of season and temperature on the air pollution (PM10 and ozone)-mortality relationship, and the influence of air pollution on the temperature-mortality relationship. Ozone and PM10 mortality risks exhibit an increasing gradient between spring, summer and heat waves. For instance, a 10 μg/m 3 increase in PM10 was associated with a 3% [Confidence interval (CI) 95% 2.1:3.9] increase in mortality during summer, and with a 14.2% [CI 95% 5.6:23.4] increase in mortality during heat waves. The heat-mortality response was slightly influenced by air pollution, especially during the most extreme heat waves. Our results suggest that air pollution warnings should take season into account, using lower thresholds during summer and heat waves. Heat warning systems may not be improved by air pollution data, as its added value would be limited, compared to the complexity it would add to the warning systems. Efforts should be made to reduce ozone and PM10 concentrations during heat waves, even when they are already below regulatory thresholds. Highlights: Ozone and PM10-mortality risks are higher during summer. Heat-mortality risk tends to be higher during polluted days. Air pollution warning systems may use seasonal thresholds. Heat warning systems may not need to use air pollution data. Ozone and PM10 levels should be decreased as much as possible during heat waves.